In vitro assessment of thyroid peroxidase inhibition by chemical exposure: comparison of cell models and detection methods - Liu, Runze; Novák, Jiří; Hilscherová, Klára (Archives of toxicology, 2024)
Disruption of the thyroid hormone (TH) system is connected with diverse adverse health outcomes in wildlife and humans. It is crucial to develop and validate suitable in vitro assays capable of measuring the disruption of the thyroid hormone (TH) system. These assays are also essential to comply with the 3R principles, aiming to replace the ex vivo tests often utilised in the chemical assessment. We compared the two commonly used assays applicable for high throughput screening [Luminol and Amplex UltraRed (AUR)] for the assessment of inhibition of thyroid peroxidase (TPO, a crucial enzyme in TH synthesis) using several cell lines and 21 compounds from different use categories. As the investigated cell lines derived from human and rat thyroid showed low or undetectable TPO expression, we developed a series of novel cell lines overexpressing human TPO protein. The HEK-TPOA7 model was prioritised for further research based on the high and stable TPO gene and protein expression. Notably, the Luminol assay detected significant peroxidase activity and signal inhibition even in Nthy-ori 3-1 and HEK293T cell lines without TPO expression, revealing its lack of specificity. Conversely, the AUR assay was specific to TPO activity. Nevertheless, despite the different specificity, both assays identified similar peroxidation inhibitors. Over half of the tested chemicals with diverse structures and from different use groups caused TPO inhibition, including some widespread environmental contaminants suggesting a potential impact of environmental chemicals on TH synthesis. Furthermore, in silico SeqAPASS analysis confirmed the high similarity of human TPO across mammals and other vertebrate classes, suggesting the applicability of HEK-TPOA7 model findings to other vertebrates.
Keywords: Autoantigens; jodidperoxidasa; Humans; autoantigeny; Endocrine Disruptors; rychlé screeningové testy; Thyroid Gland; krysa rodu Rattus; lidé; HEK293 Cells; Iodide Peroxidase; zvířata; štítná žláza; oxaziny; buněčné linie; endokrinní disruptory; Oxazines; Cell Line; proteiny vázající železo; luminol; HEK293 buňky; Iron-Binding Proteins; Rats; Luminol; Animals; High-Throughput Screening Assays